Chemically Induced Evolution of Morphological and Connectivity Characteristics of Pore Space of Complex Carbonate Rock via Digital Core Analysis. Issue 3 (7th March 2022) - Qajar, Jafar; Arns, Christoph H.
Abstract: We study the impact of reactive flow on a complex carbonate rock whose pore space was resolved by X‐ray μ‐CT. A small core plug was imaged in the original and chemically altered states. The morphology of the resolved pore space was quantified using various approaches, such as sample‐spanning cluster analysis, capillary drainage transform (CDT), and Minkowski functionals. In particular, we carefully evaluated the changes in macropore connectivity by calculating the fraction of percolated cluster, the Euler characteristic of macroporous phase, and the critical pore diameter in pre‐ and post‐alteration states. We observed that the reactive flow mainly affected larger pores in the macropore region of the sample. More importantly, a huge increase in macropore connectivity, as indicated majorly by the CDT measurements and the Euler characteristic, was observed such that the poorly connected original macropore phase was converted to well‐connected ones after the reactive flow. In addition, the increases in the macropore surface area and integral mean curvature indicated that the oomoldic and interooidal pores of the rock were dominantly enlarged by the reactive fluid. Based on direct numerical simulations on the main flow paths (i.e., the macro‐connected pore phase), strong correlations were found between changes in transport properties and the evolution of connectivity and length scales of the macropore phase, such that simple power‐law models could be used to predict with acceptable accuracy. This suggests that the evolution of transport properties of the rock was mainly controlled by the changes in the macro‐connected porosity and the critical pore diameter. Plain Language Summary: X‐ray micro‐computed tomography has attracted significant attention over the recent two decades due to its outstanding capabilities to capture the evolution of 3D structures of porous media during various processes. This study visualizes and quantifies the reactive flow‐induced changes on the images of a complex carbonate rock. To this end, we acquired images of the rock sample at the original and chemically altered states. Standard methods were used to assess the evolution of the morphology of the resolved pore space. We observed that the reactive flow mainly affected larger pores of the rock and significantly increased pore connectivity. The subsequent numerical morphology simulations revealed that the oomoldic and interooidal pores of the rock were dominantly enlarged by the reactive fluid. Based on numerical property calculations, we found that the changes in the connectivity parameters mainly controlled the evolution of transport properties of the rock. Key Points: The μ‐CT‐based connectivity and capillary drainage transform analyses indicated significant changes in macropore connectivity of a carbonate due to reactive flow The most changes in the critical pore size, Minkowski parameters, and the correlation length were found near the inlet of the sample The evolution of transport properties was mainly controlled by the changes in the macro‐connected porosity and the critical pore diameter